Persepsi Guru Tentang Peran Kepala Sekolah Sebagai Motivator di Sekolah Menengah Atas Negeri Se-Kota Pariaman: Indah Ondryma Putri, Nelfia Adi - Putri, Indah Ondryma; Adi, Nelfia (Global Action and Education for Society, 2023)
This research is motivated by the results of the author's observations which show the poor role of the principal as a motivator in public senior high schools in Pariaman City. This study aims to dig up information about Teachers' Perceptions about the Principal's Role as a Motivator in State High Schools throughout Pariaman City in terms of the aspects of Giving Rewards, Providing Examples of Discipline, Creating Fun Working Conditions/Atmosphere and Providing Encouragement to Progress. This type of research is descriptive quantitative. The population of the study were 247 teachers from State Senior High Schools in Pariaman City. A sample of 75 people was taken using a proportional stratified random sampling technique. Data was obtained by distributing questionnaires and the results were analyzed by calculating the mean score. The results showed that the teacher's perception of the principal's role as a motivator in public senior high schools in Pariaman City was in the good category, with an average score of 3.91. Based on these results, the authors suggest that the role of the principal as a motivator in public senior high schools in the city of Pariaman is maintained and needs to be increased so as to increase teacher motivation so that performance becomes efficient and effective.